STUDY ON PHYSICAL REGULARITIES OF A WIDE SPECTRUM AEROSOLS BEHAVIOR AT ITS FILTRATION THROUGH SUPER-THIN MATERIALS - Avagyan, R. M.; Haroutyunyan, G. H.; Harutyunyan, V. V.; Bagdasaryan, V. S.; Boyakhchyan, E. M.; Atoyan, V. A.; Pyuskyulyan, K. I.; Gerchikov, M. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2010)
The behavior of aerosol particles was studied at filtration through super-thin basalt fibers. Diffusion and inertial effects were investigated at the particle sedimentation using theoretical models for fiber filters taking into account the aerosol gas capture factor. Composition of radioactive aerosols was analyzed over the period of Armenian NPP operation.